A case study of physical environment and facility management in a long-term care facility - Essmiller, Mary (Kansas State University, 1994)
With the increasing older population and the expectation that an increasing number of these people will at some time reside in a long-term care facility (Urban Land Institute, 1983), there is a need to describe and evaluate the strengths and weaknesses of the physical environment and facility management in such settings. Because of the expansion in the older population, long-term care facilities are evolving in the development of resources that provide housing, nursing, and other care services for older persons. The growth in long-term care facilities warrants continued research involving the environment of such settings. In 1988, 72% of the 50 largest retirement housing operators reported that they had increased their total facilities, total units, or both during the year (Contemporary Long Term Care, 1990). The responsiveness of the environments for their residents, as well as for the staff, is of increasing importance. Because residents of long-term care facilities are no longer able to live completely independently, they depend on the help of staff members for many of life's daily functions. Assisting with dressing, toileting, bathing, and social activities are only a few tasks that staff frequently provide for residents. The humane and efficient provision of such services are the concern of residents and their families, as well as owners and administrators of such settings. While research has addressed the resident needs and functional abilities in such settings, the concerns for staff and their ability to perform effectively have received less attention. In depth inquiry and observation is warranted to describe the physical environment and facility management of long-term care facilities, as well as any relationship they may have regarding support for the staff in its caregiving role. The setting for the research was a long-term care facility located in Manhattan, Kansas. The objectives of the research were: (1) to develop a case study of this long-term care facility by observing and describing its physical environment; (2) to describe the management of the facility; and (3) to explore relationships of the physical environment and facility management. Outcomes regarding the relationship of design and management were documented, as well as any benefits with which these outcomes might be associated. The study offered additional knowledge to owners and administrators regarding how well their facility functioned, which, in turn, should help them to better understand their facility, the needs of management and staff, as well as help identify shared goals. These findings also could help formulate the design and development of future facilities, as well as help owners and administrators achieve more effective management.